Connecting digital and technology with Australia`s competitive sport obsession to achieve world-leading physical activity and high performance objectives (ASC Publishing, 2017)
Technology in Sport project: In 2016 the ASC Board instigated the Technology in Sport project to better understand how technology was impacting the Australian sport industry and how the industry needed to respond. The project had three objectives: a. To create, lead and sustain the world`s best national sport system in the use of digital and technology. b. To support sports to develop digital and technology leadership and capability. This will ensure they are connecting with their customers effectively, building their commercial potential and utilising technology and user-centred design to support growth and innovation. c. To create a digitally connected Australian sport system across the public, non-profit and private sectors. In order to achieve these objectives, three key activities were undertaken: • Establishment of an Advisory Panel consisting of external subject matter experts to advise the ASC Board on the initiative. • Undertake a research and exploratory phase to identify the national sport system`s current state and capabilities, key themes, pain points and opportunities from across national sport system stakeholders and emerging digital and technology trends from technology industry experts. • Collaboratively formulate and prioritise a system wide digital and technology vision and corresponding implementation roadmap. This document outlines the resulting vision and high level roadmap.